Oil-in-Water Self-Assembled Synthesis of Ag@AgCl Nano-Particles on Flower-like Bi(2)O(2)CO(3) with Enhanced Visible-Light-Driven Photocatalytic Activity - Lin, Shuanglong (Materials (Basel), 2016)
In this work, a series of novel flower-like Ag@AgCl/Bi(2)O(2)CO(3) were prepared by simple and feasible oil-in-water self-assembly processes. The phase structures of as-prepared samples were examined by X-ray diffraction (XRD), Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), UV-vis diffuse reflectance spectroscopy (DRS), X-ray fluorescence spectrometer (XRF), etc. The characterization results indicated that the presence of Ag@AgCl did not affect the crystal structure, but exerted a great influence on the photocatalytic activity of Bi(2)O(2)CO(3) and enhanced the absorption band of pure Bi(2)O(2)CO(3). The photocatalytic activities of the Ag@AgCl/Bi(2)O(2)CO(3) samples were determined by photocatalytic degradation of methylene blue (MB) under visible light irradiation. The Ag@AgCl (10 wt %)/Bi(2)O(2)CO(3) composite showed the highest photocatalytic activity, degrading 97.9% MB after irradiation for 20 min, which is over 1.64 and 3.66 times faster than that of pure Ag@AgCl (calculated based on the equivalent Ag@AgCl content in Ag@AgCl (10 wt %)/Bi(2)O(2)CO(3)) and pure Bi(2)O(2)CO(3), respectively. Bisphenol A (BPA) was also degraded to further prove the degradation ability of Ag@AgCl/Bi(2)O(2)CO(3). Photocurrent studies indicated that the recombination of photo-generated electron–hole pairs was decreased effectively due to the formation of heterojunctions between flower-like Bi(2)O(2)CO(3) and Ag@AgCl nanoparticles. Trapping experiments indicated that O(2)(−), h(+) and Cl° acted as the main reactive species for MB degradation in the present photocatalytic system. Furthermore, the cycling experiments revealed the good stability of Ag@AgCl/Bi(2)O(2)CO(3) composites. Based on the above, a photocatalytic mechanism for the degradation of organic compounds over Ag@AgCl/Bi(2)O(2)CO(3) was proposed.